The Influence of Peer and Parental Support on Adolescent Mental Health - Srinoviyanti Malanding (Generasi Sains Indonesia, 2025)
Adolescent mental health has become an important global concern due to increasing levels of anxiety, depression, and emotional instability during developmental transitions. This study aimed to examine the influence of peer and parental support on adolescent mental health, particularly anxiety, depression, and self-esteem. A mixed-methods explanatory sequential design was employed involving 500 adolescents for quantitative analysis and 30 participants for qualitative interviews. Quantitative findings revealed that both peer and parental support significantly reduced anxiety and depression while positively influencing self-esteem. Parental support demonstrated a stronger predictive contribution compared with peer support. The qualitative findings further showed that adolescents perceived peers as sources of emotional companionship, whereas parents provided emotional security and stability. The novelty of this study lies in identifying the synergistic interaction between peer and parental support in strengthening adolescent psychological well-being. The findings imply that adolescent mental health interventions should integrate family-based and peer-support approaches to promote emotional resilience and sustainable psychological development.